The Referential Function of the "Golden Bough" Imagery in “Sailing to Byzantium” from the Perspective of Conceptual Integration Theory - Zhang, Yi (Bilingua, 2026)
The purpose of this study is to analyze the referential function of the "golden bough" imagery in W.B. Yeats's “Sailing to Byzantium” and to find out how conceptual integration generates meaning. It adopts literature analysis, using Yeats' poetry and related intertextuality as materials to identify three psychological spaces and analyze their structures through conceptual integration theory (CIT). The research results indicate that "golden branches" have a referential function, constructed by the integration of concepts in the text and their emerging structures. It appears as a 'living but lifeless' entity, possessing materiality, biology, artistry, and sacredness, and cannot be understood solely by the distinction between nature and artificiality.